Study of the effective transverse momentum of partons in the proton using prompt photons in photoproduction at HERA - Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; et al. (2001)
The photoproduction of prompt photons, together with an accompanying jet, has been measured with the ZEUS detector at HERA using an integrated luminosity of 38.6 pb-1. A study of the effective transverse momentum, (kT), of partons in the proton, as modelled within the framework of the PYTHIA Monte Carlo, gives a value of (kT) = 1.69 ± 0.18 -0.20+0.18 GeV for the γp centre-of-mass energy range 134 < W < 251 GeV. This result is in agreement with the previously observed trend in hadron-hadron scattering for (kT) to rise with interaction energy. © 2001 Elsevier Science B.V.